Macrosomia: ACOG Practice Bulletin, Number 216 (Obstetrics and gynecology (New York. 1953), 2020)
Suspected macrosomia is encountered commonly in obstetric practice. As birth weight increases, the likelihood of labor abnormalities, shoulder dystocia, birth trauma, and permanent injury to the newborn increases. The purpose of this document is to quantify those risks, address the accuracy and limitations of methods for estimating fetal weight, and suggest clinical management for a pregnancy with suspected macrosomia. This document has been revised to include recent literature and updated information on the prevention of macrosomia.